Effect of fermented cassava tuber on the gene expression of PI3K/Akt signaling and AMPK pathway in STZ-NA-induced diabetic rats - Kusuma, Rio Jati; Puspaningtyas, Desty Ervira; Sari, Puspita Mardika (Emerald Publishing, 2022)
Purpose: The downstream insulin signaling, such as phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) pathway, is an important step for skeletal glucose disposal through the translocation of glucose transporter (GLUT)-4. In addition, the master of energy regulator adenosine monophosphate-activated kinase (AMPK) is also involved in GLUT-4 translocation, independent from the PI3K/Akt pathway. Fermented cassava tuber or gatot is a traditional food from Indonesia with antihyperglycemic properties. However, the molecular mechanism leading to this effect is unclear. Therefore, this paper aims to evaluate whether the antidiabetic activity of gatot is through PI3K/Akt dependent or AMPK pathway. Design/methodology/approach: Diabetes mellitus was induced in 20 male Wistar rats by intraperitoneal injection of 65 mg/kg body weight streptozotocin and 230 mg/kg body weight nicotinamide. Diabetic rats were randomly allocated into four groups; negative control, positive control (metformin 100 mg/kg body weight), fermented cassava diet replacing 50% of carbohydrate (FC-50) and 100% of carbohydrate (FC-100) in the diet. Serum glucose, insulin and lipid profile were analyzed before and after four weeks of intervention. Genes expression of PI3K subunit alpha, PI3K subunit beta, PI3K regulatory subunit, Akt and AMPK were analyzed using real time polymerase chain reaction (PCR). GLUT-4 protein expression was performed using immunohistochemistry. Findings: There is a significant difference (p = 0.000) in serum glucose, insulin, total cholesterol, triglyceride, high density lipoprotein (HDL)-cholesterol and LDL-cholesterol between groups. Skeletal AMPK gene expression was higher and significantly different between FC-100 (p = 0.006) and healthy control groups. No significant difference was observed in the messenger ribonucleic acid (mRNA) expression of the PI3K/Akt pathway among groups. GLUT-4 expression was highly expressed in a positive control group followed by FC-100. Research limitations/implications: This paper did not characterize the bioactive component that is responsible for increasing mRNA expression of AMPK. This paper also did not analyze the phosphorylation of PI3K/Akt and AMPK that are important in activating the protein. Originality/value: To the best of the authors’ knowledge, this is the first study that showed the antidiabetic activity of traditional fermented food is through AMPK-dependent activity.